The role of the public interest in competition law a consideration of the public interest in merger control and exemptions in South Africa and how the public interest plays a more important role in the competition laws of South Africa and of developi - Teague, Ian Graeme (Department of Commercial Law, 2014)
Includes bibliographical references.